Housing Commodification in the Balkans: Serbia, Slovenia and Greece - Vilenica, Ana; Katerini, Tonia; Filipovič Hrast, Maša (Κοινωνική Πολιτική, 2021)
In Balkans region, uneven development under global capitalism has led to significant differences in housing commodification patterns, related (social and housing) policy and associated inequalities. In this article we describe commodification patterns in Slovenia, Serbia and Greece by considering the diversity existing in the semiperiphery. We do this by comparing processes of privatisation of housing, development of the rental sector, strategies to homeownership and legal frameworks of protection of property and housing rights. We find some similarities in specific individual and familial commodification patterns and also pronounced inequalities but also semiperiphery diversity, which has been produced and maintained by the presence (or absence) of policies and state care provided for certain vulnerable groups. These diverse aspects arise from specific local, regional and global histories of housing struggles that mean the responses to them have varied. In this research, we show that Balkans semiperipheral territories must not be regarded as a passive background but as a landscape in which active agents participate in creating and transforming commodification patterns.